(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents the results of a study on the effectiveness of an author’s methodology of physical therapy for patients with traumatic brain injuries (TBI) in inpatient settings. The developed methodology is based on a modular principle and includes three main blocks: motor learning, coordination training, and cognitive learning using computerized systems with biofeedback. The study was conducted at the Military Medical Clinical Center of the Central Region in Vinnytsia, involving 30 male patients aged 20-35 years with mild TBI and diffuse axonal injuries. Participants were divided into two groups: control (standard rehabilitation program) and experimental (author’s methodology). The effectiveness of the methodology was assessed by indicators of pain level (VAS), self-assessment of functional state (WAM), anxiety (Spielberg-Khanin test), muscle strength (Motricity Index), fatigue level (Borg scale), balance (Berg scale), neurological status (NOS-TBI), visual-spatial orientation (Walking Corsi Tapping), and cognitive functioning (Rancho Los Amigos). The results confirmed a statistically significant advantage of the author’s methodology in all studied parameters, including a 69,1% reduction in pain level, 62,8% improvement in functional state, 40,6% reduction in anxiety, 87,8% improvement in balance, 50,9% reduction in neurological deficit, and 76,1% increase in quality of life. The proposed physical therapy methodology demonstrates high effectiveness in restoring motor, coordination, and cognitive functions of patients with TBI in inpatient settings. The individualized approach, active exercises, and systematic training helped reduce patients’ pain, improve movement coordination, and contributed to the restoration of cognitive functions. The results confirm the importance of an integrated approach to the rehabilitation of patients with TBI, which should include work on both physical capabilities and cognitive functions, considering the specifics of traumatic brain lesions and their multifactorial impact on the human body.